Theoretical and methodological principles of the prospective system of monetary support for servicemen of the Armed Forces of Ukraine - Gorodianska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article presents a model of the organizational structure of a promising system of monetary support for servicemen of the Armed Forces of Ukraine, and based on it, the theoretical and methodological foundations of this system were formed. It is proposed to form a promising system of monetary support for military personnel based on interdependent components that create an organizational structure. It was established and substantiated, using system-logical and functional approaches to the tasks, that the components of the perspective system of monetary support for military personnel should be parametric, informational, functional and technological components. The article defines and substantiates the content and purpose of each of the components. In the context of the modern military-political vision of the Armed Forces of Ukraine, it is claimed that the parametric component should reproduce the connection of the system with external factors and principles of system construction: general legal, branch and special. It is argued that the leading principles should be the rule of law, people- centrism, justice and legal equality, unity and differentiation of legal regulation, guaranteeing decent amounts of payments, etc. The information component should reproduce the information objects and data of the system, the size and conditions of monetary payments to servicemen. The main conditions for monetary support to servicemen of the Armed Forces of Ukraine should be: qualification level, professional training and conscientious performance of assigned duties. The functional component should reproduce the structure and content of payments and social guarantees to military personnel. It has been established and substantiated that the payments are divided into basic by military rank and by years of service in the corresponding rank, and into allowances and additional payments according to the structure. The technological component reproduces the logic of the technological process of forming the system of monetary support for military personnel, mechanisms and tools for its implementation. It is claimed that the technological process of providing monetary support to military personnel should be carried out in the environment of a modern automated accounting and calculation system.
Keywords: organizational structure, model, military serviceman, monetary support, perspective system, parametric component, informational component, functional component, technological component